CAREER DEVELOPMENT SUPPORT MODEL FOR WOMEN AFTER CHILDBIRTH - Brinkmane-Brimane, Eva; Dislere, Vija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article addresses the problem of obstacles to use the labour potential of women after childbirth. The aim of the study is to develop a post-natal career development support model for modern women, based on research on barriers to women's career advancement and promoting the balance of life between women's integration into the labour market and child upbringing. The study was developed in the Latvia University of Life Sciences and Technologies, the Institute of Education and Home Economics within the Master study programme Career Counsellor. A study on barriers to women's career development after childbirth were involved 647 respondents. An expert evaluation of the career development model for women was carried out with the participation of 4 experts in the field of career counselling. As a result of the study, the main obstacles for working age women / mothers were: lack of childcare services (245 respondents' answers); number of vacancies in the place of residence (151 respondents); insufficient partner support (110 respondents' answers). Experts' assessment allowed to conclude that the Career Development Support Model developed by the authors promotes a work-life balance between family life and work for women after childbirth. Results of the research could be used in the work of adult career counsellors.